2006
DOI: 10.1227/01.neu.0000209653.82936.96
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Posttraumatic Acute Subdural Hematoma in Elderly Patients on Anticoagulation

Abstract: A suspicion of DASH should be raised in elderly, anticoagulated, mild TBI patients, including those who present to the emergency department with Glasgow Coma Scores of 15 and normal computed tomographic scans after injury. Based on our experience, we recommend that elderly, anticoagulated mild TBI patients should be admitted for 24 to 48 hours of observation after injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 42 publications
1
47
0
Order By: Relevance
“…One study found that these patients deteriorated due to delayed acute subdural hematoma from 9 hours to 3 days after traumatic brain injury. 3) Similarly, the time from trauma to admission was significantly longer in the bleeding tendency group (mean 32.7 hours) compared with control group (mean 9.7 hours) in the present series. Therefore, cautious follow up using head CT is recommended in patients who received anticoagulant or anti-aggregation therapy.…”
Section: Discussionsupporting
confidence: 47%
See 4 more Smart Citations
“…One study found that these patients deteriorated due to delayed acute subdural hematoma from 9 hours to 3 days after traumatic brain injury. 3) Similarly, the time from trauma to admission was significantly longer in the bleeding tendency group (mean 32.7 hours) compared with control group (mean 9.7 hours) in the present series. Therefore, cautious follow up using head CT is recommended in patients who received anticoagulant or anti-aggregation therapy.…”
Section: Discussionsupporting
confidence: 47%
“…The symptoms are relatively mild at onset in these patients. 3,6) The Glasgow Coma Scale score on admission was 2.1 points better in the bleeding tendency group compared with control group in the present series.…”
Section: Discussionmentioning
confidence: 38%
See 3 more Smart Citations